Chondrosarcoma of maxilla - Gawande, Madhuri (J Oral Maxillofac Pathol, 2014)
Chondrosarcoma (CHS) is a rare malignant neoplasm of the jaws. Based on the morphologic features alone, a correct diagnosis of CHS may be difficult. Therefore, correlation of radiological and clinicopathological features are mandatory for the diagnosis of CHS. A case of CHS of the maxilla is reported. A brief discussion on the etiopathogenesis, radiologic and histologic presentation of the tumor and the treatment modalities of this unusual tumor is discussed.